Synthesis, Characterization and Performance Study of Biomass Derived Supercapacitor Electrode. Issue 5 (19th May 2021) - Tripathi, Manoj; Bhatnagar, Ashish; Pandey, Krishna Kumar; Ganesan, P.
Abstract : Energy storage using biomass derived electrodes is very interesting and potential field. Replacing commercial activated carbon with biomass derived char may reduce the cost of electrode without affecting the performance significantly. In present study, oil palm shell (OPS) derived char synthesized by microwave pyrolysis is used to prepare an electrode and its performance as an electrode is studied. OPS and OPS char is characterized using ultimate & proximate analysis, TGA-DTA, FT-IR and SEM. Carbon percent in OPS char is found to be 59.42 wt.% as compared to 42.59 wt.% for OPS. TGA affirms that OPS char is thermally more stable than OPS. SEM images incite significant morphological change upon exposure of microwave radiation on OPS. It further shows that smaller pores in OPS have developed into larger pores in OPS char. Adsorption-desorption study of OPS char confirms the porous nature of OPS char. BET surface area of OPS char is 265.90 m 2 g −1 . Electro-chemical study is conducted with three electrode system. Specific capacitance of OPS char derived electrode is 203.30 F g −1 . Charging-discharging cycle lowered the specific capacitance. The drop is less significant at lower scan rate. The energy storage cost is also determined which is $ cent 0.05/F.